A qualitative approach to the dynamics of a higher education institution from the perspective of teachers - Cortez-Félix, Gustavo Enrique (Consorcio de Universidades Mexicanas A.C., 2014)
This research departs from the interest to determine which processes and incidents of the dynamics of a Mexican public university become relevant as perceived by academics, as well as to explore how these events form or change identities. A qualitative grounded theory research design was made, in which deep interviews where done to eighteen teachers from different programs, the speeches were analyzed in relation to descriptions, references, processes, events, structural and government dimension, political dimension, labor dimension, academic dimension, among other units. As a result we display a diagram showing the different possible routes reported as experiences of the respondents where academic and professional dimensions touch on relevant processes in their pathways, also a description from the voice of the teachers is presented. Furthermore, although teaching is the primarily conducted activity at the university, the institutional dynamics generates different arrangements not without promoting frictions and tensions in teachers as they have to respond to the pressures of political and labor dimensions.